Pencabutan Public Service Obligation pada Kereta Rail Listrik dan Kinerja Finansial Operator - Dwi Ardianta Kurniawan; Hengki Purwoto; Agunan Samosir (Institut Transportasi dan Logistik Trisakti, 2022)
The issue of Public Service Obligation for Jabodetabek Commuter Line is indicated off-target due to 60% of its users are considered employed or have income. However, the Obligation is one of the revenue sources for railway operators. The retraction of the Obligation could reduce the railway operators’ overall revenue. This study analyzes the effect of the retraction of Public Service Obligation to the financial of Jabodetabek commuter line operators. The method used in the study was by simulating the passengers’ volume and income based on the elasticity of passengers to the fare changes. The results show that the volume of Jabodetabek Commuter Line users of the employed or have income groups will not be significantly affected by the retraction of Public Service Obligation due to their ability in paying and their inelasticity commuter line trip. The simulation also shows that the revenue from other tariff aside from the Public Service Obligation is the largest compared to other revenue sources with a fairly high elasticity value (-0.6). The result indicates that other tariffs aside from Public Service Obligation are potential to be the commuter line operators’ major revenue.